TECHNOLOGY AND EQUITY MARKET CO-MOVEMENTS IN THE ASIA-PACIFIC: EVIDENCE FROM APEC INDICES (Lex localis - Journal of Local Self-Government, 2025)
The Asia-Pacific Economic Cooperation (APEC) region is a vibrant economic center that has been influenced more by the technological development and digitalization. The paper explores the relationship between equity markets and technology indices in the APEC economies with the focus on co-movement dynamics in reaction to five key global crises (Oil Crisis, Climate Crisis, COVID-19 pandemic, Russia-Ukraine War, and Iran-Israel War). The study uses wavelet coherence analysis to study the time development of market interactions during these crises. The findings show that there has been a gradual rise in the level of technological integration and synchronization among the economies of the APEC, especially between the Climate Crisis and the COVID-19 pandemic. The analysis highlights how digital infrastructure and innovation policies can be used to enhance market connections and improve regional resilience. The long-term consistency of technology and equity markets implies that the integration of technology is now an essential part of the coordination of the economy in the region. The paper ends by making policy recommendations on how to develop sustained growth in technology, investment patterns and business planning in the APEC economies with special focus on the role of technology in ensuring economic stability and growth in the region.